Long-term use of proton pump inhibitors does not affect ectopic and metachronous recurrence of gastric cancer after endoscopic treatment. (1st February 2020) - Oura, Hirotaka; Matsumura, Tomoaki; Kawasaki, Yohei; Okimoto, Kenichiro; Ishikawa, Kentaro; Kaneko, Tatsuya; Tokunaga, Mamoru; Oike, Tsubasa; Imai, Yushi; Yokoyama, Yuya; Akizue, Naoki; Maruoka, Daisuke; et al.
Abstract: Objective: Long-term administration of proton pump inhibitors (PPIs) after eradication of Helicobacter pylori infection has been reported to increase the risk for development of gastric cancer (GC). We investigated whether long-term administration of PPI affects ectopic and metachronous recurrence of GC after endoscopic treatment. Methods: Participants were 687 patients who underwent endoscopic treatment for GC from January 2005 to March 2018. Questionnaire surveys and medical record reviews of medications, including PPIs, H2 receptor antagonists and low-dose aspirin (LDA) were conducted for all patients. The influence of PPI in ectopic and metachronous recurrence of GC was evaluated with Cox's proportional hazard analysis. Results: Patients who did not respond to the questionnaire and those who underwent additional treatment after endoscopic treatment were excluded from analyses; 418 patients were included. During an average observation period of 1608 days (range, 375–4993 days), 136 patients (32.5%) took PPIs for more than 1 year and 94 took PPIs for more than 3 years; of those, 40 had ectopic and metachronous recurrences. Cox's proportional hazards analysis revealed that long-term use of PPIs (for both 1 year and 3 years) was not a risk factor for recurrence. In addition, age, severity of gastric atrophy, long-term use of LDA, current infection with H. pylori, and cure achieved with the first endoscopic treatment were also not risk factors for recurrence. Conclusions: Long-term use of PPIs does not affect ectopic and metachronous recurrence of GC after endoscopic treatment.